1976
DOI: 10.1002/neu.480070405
|View full text |Cite
|
Sign up to set email alerts
|

A mutant of Paramecium with increased relative resting potassium permeability

Abstract: Fast-2, a membrane mutant of Paramecium aurelia, is due to a single-gene mutation and has behavioral abnormalities. Intracellular recordings through changes of external solutions were made. The mutant membrane hyperpolarized when it encountered solutions with low K+ concentration. This hyperpolarization and other associated activities were best observed in Ca- or Na-solutions devoid of K+. Membrane potential was plotted against the concentration of K+ (0.5 to 16 mM) in solutions of fixed Na+ or Ca++ concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…The increase of external concentration of these cations depolarize the resting membrane. On the other hand, the K-permeability is considered the major permeability of the resting membrane in P. caudatum (Naitoh and Eckert, 1968a;Eckert, Naitoh and Machemer, 1976) and P. tetraurelia (Satow and Kung, 1976a). The present work supports the latter view.…”
Section: Discussionsupporting
confidence: 84%
“…The increase of external concentration of these cations depolarize the resting membrane. On the other hand, the K-permeability is considered the major permeability of the resting membrane in P. caudatum (Naitoh and Eckert, 1968a;Eckert, Naitoh and Machemer, 1976) and P. tetraurelia (Satow and Kung, 1976a). The present work supports the latter view.…”
Section: Discussionsupporting
confidence: 84%
“…Despite the loss of attraction in Na-acetate, we believe that I Na(Ca) plays no significant role in chemoresponse to acetate because the loss of chemoresponse in K + -free (Na) acetate solutions is a secondary effect of the mutation. Cam 11 in K + -free media has an extremely low resting membrane potential [near the equilibrium potential for K + (E K ) (Satow and Kung, 1976)], which prevents the cell from responding with an adequate hyperpolarization for the on-response or depolarization of the off-response.…”
Section: Acetate T-mazesmentioning
confidence: 99%
“…Three of these (spots B, D, and F) are phosphonolipids, and the other three (spots A, C, and E) have the more common phosphodiester linkages at the headgroup. It appears most likely that the three pairs (spots A and B, C and D, and E and F) represent the phospholipid and phosphonolipid derivatives of three long-chain bases, sphingosine, dihydrosphingosine, and phytosphingosine (21 (30). The baAffna double mutant showed the same alteration ofciliary membrane phospholipid and sphingolipid composition as did the baA single mutant (Table 1).…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, over 300 behavioral-mutant lines have been isolated mapping to more than 25 complementation groups (26,27). The electrophysiological correlates of these behavioral mutations have, in many cases, been determined (28)(29)(30) (33), and hydrostatic pressure (34) have suggested that lipids also affect ion channel activity in Paramecium. In this report we now show that the functions ofvoltage-sensitive ion channels in the excitable membrane of Paramecium appear to be affected by a mutationally induced change in the phospholipid composition of the ciliary membrane.…”
mentioning
confidence: 99%